Physics Potential of Long-Baseline Experiments - Sanjib Kumar Agarwalla (Advances in High Energy Physics)
The discovery of neutrino mixing and oscillations over the past decade provides firm evidence for new physics beyond the Standard Model. Recently, θ13 has been determined to be moderately large, quite close to its previous upper bound. This represents a significant milestone in establishing the three-flavor oscillation picture of neutrinos. It has opened up exciting prospects for current and future long-baseline neutrino oscillation experiments towards addressing the remaining fundamental questions, in particular the type of the neutrino mass hierarchy and the possible presence of a CP-violating phase. Another recent and crucial development is the indication of non-maximal 2-3 mixing angle, causing the octant ambiguity of θ23. In this paper, I will review the phenomenology of long-baseline neutrino oscillations with a special emphasis on sub-leading three-flavor effects, which will play a crucial role in resolving these unknowns. First, I will give a brief description of neutrino oscillation phenomenon. Then, I will discuss our present global understanding of the neutrino mass-mixing parameters and will identify the major unknowns in this sector. After that, I will present the physics reach of current generation long-baseline experiments. Finally, I will conclude with a discussion on the physics capabilities of accelerator-driven possible future long-baseline precision oscillation facilities.